2016
DOI: 10.1080/13607863.2016.1179261
|View full text |Cite
|
Sign up to set email alerts
|

The use of the truth and deception in dementia care amongst general hospital staff

Abstract: The study adds to the growing research regarding the use of lies in dementia care by considering the decision-making processes for staff in general hospitals. Various factors influence how staff choose to respond to patients with dementia and whether deception is used. Similarities and differences with long-term dementia care settings are discussed. Clinical and research implications include: opening up the topic for further debate, implementing staff training about communication and evaluating the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 23 publications
1
52
0
1
Order By: Relevance
“…A recent meta-synthesis of qualitative research identified over-arching themes related to NAs’/AHWs’ challenges when caring for hospitalized individuals with dementia: Overcoming Uncertainty When Delivering Care, Inequality in the Quality of Care Provided to Individuals With Dementia, Recognizing the Benefits of Person-Centered Care but Not Being Able to Deliver it Due to Constraints of the Environmental and Wider Organizational Context , and Need for Training (Turner, Eccles, Elvish, Simpson, & Keady, 2015). Additional findings emphasize gaps in knowledge among NAs/AHWs pertaining to dementia care, particularly issues related to communication with and responding to behaviors of individuals with dementia (Clissett, Porock, Harwood, & Gladman, 2013; Gaugler & Wocken, 2014; Turner, Eccles, Keady, Simpson, & Elvish, 2016; Turner et al, 2015). …”
mentioning
confidence: 94%
“…A recent meta-synthesis of qualitative research identified over-arching themes related to NAs’/AHWs’ challenges when caring for hospitalized individuals with dementia: Overcoming Uncertainty When Delivering Care, Inequality in the Quality of Care Provided to Individuals With Dementia, Recognizing the Benefits of Person-Centered Care but Not Being Able to Deliver it Due to Constraints of the Environmental and Wider Organizational Context , and Need for Training (Turner, Eccles, Elvish, Simpson, & Keady, 2015). Additional findings emphasize gaps in knowledge among NAs/AHWs pertaining to dementia care, particularly issues related to communication with and responding to behaviors of individuals with dementia (Clissett, Porock, Harwood, & Gladman, 2013; Gaugler & Wocken, 2014; Turner, Eccles, Keady, Simpson, & Elvish, 2016; Turner et al, 2015). …”
mentioning
confidence: 94%
“…Furthermore, the nurses and care workers perceived lies and deception to be acceptable in the context of certain interactions with older people with severe dementia. Although the acceptability and ethicality of deception in dementia care remains an area of heated debate, lying is viewed as therapeutic because the care provider's intent is to eliminate harm, control behaviour disorders, and reassure. Deceptive practice has been shown to be prevalent in long‐term care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Seaman and Stone (2017) highlight the complexities of deception in the context of dementia, noting that caring for people living with dementia involves dynamic interactions among a network of care providers, across various different settings. Collaborative, shared decision-making regarding the best interest of the person living with dementia is therefore critical (Tullo et al, 2015;Turner et al, 2017). In this way all key stakeholders are involved and are aware of the decision made regarding lying promoting consistency in approach (James & Caiazza, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These authors justify the use of therapeutic lying once the aim is to improve the life of the recipient and developed a set of 12 ethical guidelines governing its use in formal care. Health care professionals however often face challenges in interpreting ethical guidelines when communicating with patients with dementia (Day, James, Meyer, & Lee, 2011;Elvish, James, & Milne, 2010;Tuckett, 2012;Turner et al, 2017). O'Connor, James and Caiazza (2017) recognising the complexities and challenges surrounding the use of therapeutic lying in the real world of practice, created a hierarchical needs-based decision framework for health care professionals.…”
Section: Literature Reviewmentioning
confidence: 99%